Draft genome sequence of colistin-resistant and extended-spectrum β-lactamase (ESBL)-producing multidrug-resistant Escherichia coli isolated from poultry meat. (December 2021) - Yasir, Muhammad; Qureshi, Arooj K.; Kensarah, Eman Ahmed; Bibi, Fehmida; Al-Zahrani, Ibrahim A.; Abd El Ghany, Moataz; Azhar, Esam I.
ABSTRACT: Objectives: The presence of multidrug-resistant bacteria in the food chain represents a major public-health concern and has significant economic repercussions. Here we describe the draft genome sequence of serotype O21:H16, multilocus sequence typing (MLST) ST3270 and ribosomal MLST rST120701, multidrug-resistant Escherichia coli Ch7_4SIAU, which was isolated from poultry meat collected from a local market in Jeddah, Saudi Arabia. Methods: Ch7_4SIAU was grown on MacConkey agar and was identified using matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry (MALDI-TOF/MS). An Illumina MiSeq platform was used to generate 2.4 million paired-end reads of 150 bp. Results: The draft genome of Ch7_4SIAU is ∼5.1 Mb with a GC content of ∼50% and contains five plasmid replicons [ColpVC, IncFII, IncHI2, IncI(Gamma) and IncX1]. The isolate is resistant to third- and fourth-generation cephalosporins. It carries the mobile colistin resistance gene mcr-1.1 and the extended-spectrum β-lactamase (ESBL) gene bla CTXM-15 as well as the astA gene encoding enteroaggregative E. coli heat-stable enterotoxin 1 (EAST-1). Conclusion: This report presents the first draft genome of ESBL-positive E. coli isolated from poultry meat in Saudi Arabia. The findings can be used as a reference for genomic epidemiological studies of antimicrobial resistance in Enterobacteriaceae in the local food chain.